2015
DOI: 10.1590/s1806-37132015000004367
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life in patients with advanced non-small cell lung carcinoma treated with a combination of carboplatin and paclitaxel

Abstract: OBJECTIVE: Non-small cell lung carcinoma (NSCLC) is the most common type of lung cancer. Most patients are diagnosed at an advanced stage, palliative chemotherapy therefore being the only treatment option. This study was aimed at evaluating the health-related quality of life (HRQoL) of advanced-stage NSCLC patients receiving palliative chemotherapy with carboplatin and paclitaxel. METHODS: This was a multiple case study of advanced-stage NSCLC outpatients receiving chemotherapy at a public hospital in Rio de J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
0
19
0
3
Order By: Relevance
“…A cross-sectional design was adopted in 55.6% (n=10) of the studies. Non-controlled prospective, "before and after" studies assessed QoL before and after chemotherapy 9,14 , before three cycles of chemotherapy 26 , before and after lung resectioning 21,22 , before and after physiotherapy 20 , before starting treatment and two and four months after the first evaluation and/or the beginning of treatment 27 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional design was adopted in 55.6% (n=10) of the studies. Non-controlled prospective, "before and after" studies assessed QoL before and after chemotherapy 9,14 , before three cycles of chemotherapy 26 , before and after lung resectioning 21,22 , before and after physiotherapy 20 , before starting treatment and two and four months after the first evaluation and/or the beginning of treatment 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently adopted was specific for people with cancer, EORTC QLQ-C30, although it was used in less than half of the articles. Its LC-13 complementary module was used in two studies 15,26 because it is specific for lung cancer, evaluating QoL for the particular symptoms of this disease. It is therefore recommended to combine these scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though systemic chemotherapy has associated side-effects, multiple studies have shown improved survival and QoL in patients with IIIB/IV NSCLC. [101][102][103][104] Though this review will not cover chemotherapy in any depth, several studies have shown survival, QoL, and symptomatic benefits from cytotoxic chemotherapy regimens including vinblastine, docetaxel, vinorelbine, gemcitabine, and pemetrexed. [105][106][107][108][109][110] Addressing concurrent chemoradiation, in 191 patients with stage III NSCLC, adding concurrent radiation improved survival (3 months) and maintained QoL, at the expense of increased hospital admissions.…”
Section: Benefits Of Palliative Care In Lung Cancermentioning
confidence: 99%
“…One such study involves the use of a lectin, Maackia amurensis agglutinin (MAA), as an adjuvant and shows its efficacy in different cancers (Lalli et al, 2015). Other studies show combinations of different drugs with paclitaxel to enhance its efficacy, like dasatinib (Xiao et al, 2015) and carboplatin (Avelino et al, 2015).…”
Section: Clinical Trialsmentioning
confidence: 99%